Searching for Truth in Vojvodovo from the Perspective of Revivalist Movements - Pavlásek, Michal (Lidé města, 2011)
This article is dedicated to the interpretation of the influence of religious revival movements on the religiosity of Czech (and Slovak) Protestant communities in southeastern Europe in the 19th and 20th century. In addition, it monitors the effect of the Blue Cross Movement and the Free Reformed Church in the village of St. Helena (located in Romanian Banat). The influence of the spiritual principles of religious revival movements led to a schism within the Evangelical community. The author then applies the wider context of the revival of the reformed church to the what is known about the content of the faith of Czech residents in the Bulgarian village of Vojvodovo. The hypothesis on the decisive influence of revival movements on religiosity of Czech Protestants is being gradually verified and validated. The article attempts to capture the hitherto neglected importance of revival religious movements for the spirituality of Czech and Slovak Protestant enclaves in southeastern Europe.